Fast Travel, Expensive to Sustain? An Evaluation of the Jakarta-Bandung High-Speed ​​Rail Policy - Nugraha, Muhammad Bintang (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The Jakarta–Bandung High-Speed ​​Rail (Whoosh) project is a National Strategic Project that represents an effort to modernize Indonesia's national transportation system. This study aims to evaluate the alignment of the Whoosh development policy with the direction of national development as outlined in the National Long-Term Development Plan (RPJPN) and the National Medium-Term Development Plan (RPJMN), and to identify policy dynamics and sustainability challenges. This study uses a qualitative approach with a descriptive-analytical research type. The data used are secondary data obtained through literature studies, including regulatory documents, development planning documents, scientific journals, official reports, and media coverage. The analysis was conducted using David Easton's Political System Model, which includes input, process (conversion), output, feedback, and policy environment stages. The results show that the Whoosh project is substantially in line with the transportation modernization and national connectivity improvement agenda in the RPJMN. However, the project's contribution to equitable development as mandated in the RPJPN is still not optimal, marked by the concentration of benefits around the station area and the existence of serious challenges in the aspects of financing and operational sustainability. Therefore, it is necessary to strengthen policy governance, integrate transportation modes, and adjust financing strategies so that the Whoosh project can provide more inclusive and sustainable benefits for national development.